Applying Educational Theory and Best Practices to Solve Common Challenges of Simulation‐based Procedural Training in Emergency Medicine. (27th December 2019) - Cassara, Michael; Schertzer, Kimberly; Falk, Michael J.; Wong, Ambrose H.; Hock, Sara M.; Bentley, Suzanne; Paetow, Glenn; Conlon, Lauren W.; Hughes, Patrick G.; McKenna, Ryan T.; Hrdy, Michael; Lei, Charles; et al.
Abstract: Objectives: Procedural competency is an essential prerequisite for the independent practice of emergency medicine. Multiple studies demonstrate that simulation‐based procedural training (SBPT) is an effective method for acquiring and maintaining procedural competency and preferred over traditional paradigms ("see one, do one, teach one"). Although newer paradigms informing SBPT have emerged, educators often face circumstances that challenge and undermine their implementation. The goal of this paper is to identify and report on best practices and theory‐supported solutions to some of these challenges as derived using a process of expert consensus building and reviews of the existing literature on SBPT. Methods: The Society for Academic Emergency Medicine (SAEM) Simulation Academy SBPT Workgroup convened approximately 8 months prior to the 2019 SAEM Annual Meeting to perform a review of the literature and participate in a consensus‐building process to identify solutions (in the form of best practices and educational theory) to these challenges faced by educators engaging in SBPT. Results and Analysis: Thirteen distinct educational challenges to SBPT emerged from the expert group's primary literature reviews and consensus‐building processes. Three domains emerged upon further analysis of the 13 challenges: learner, educator, and curriculum. Six challenges within the "learner" domain were selected for comprehensive discussion in this paper, as they were deemed representative of the most common and most significant threats to ideal SBPT. Each of the six challenges aligns with one of the following themes: 1) maximizing active learning, 2) maintaining learner engagement, 3) embracing learner diversity, 4) optimizing cognitive load, 5) promoting mindfulness and reflection, and 6) emphasizing deliberate practice for mastery learning. Over 20 "special treatments" for mitigating the impact of the 13 challenges were derived from the secondary literature search and consensus‐building process prior to and during the preconference workshop; 11 of these that best address the six learner‐centered challenges are explored, including implications for educators involved in SBPT. Conclusions/Implications for Educators: We propose multiple consensus‐generated solutions (in the form of best practices and applied educational theory) that we believe are suitable and well aligned to overcome commonly encountered learner‐centered challenges and threats to optimal SBPT.